Perancangan Dokumen Sistem Manajemen Mutu ISO 9001:2015 di CV.XYZ - Alex Randy Samuel Sitorus; Jani Rahardjo (Jurnal Titra, 2022)
CV. XYZ is a manufacturing company that processes plastic as raw materials into household products. Form interviews with the company, it was revealed that the company has not planned to design ISO 9001:2015 because it has not been committed. This study aims to identify and complete the documents and deficiencies required for Iso 9001:2015 certification. Documents and data needed for research were obtained by interviewing the owner of the company, workers in the company and observation. The first step is an analysis of conformity to the ISO to find out what percentage of document readiness the company has . The second step is to design the required clause. The initial gap was found to be 8%. Then the appropiate clause will be directly inserted into the new design and the unfulfilled ones will be redesigned. The design is carried out for clauses 4 to 9. After design, the final result of compliance with ISO 9001:2015 is 83%.